2022
DOI: 10.3390/jcm11030802
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Salivary Gland Diseases: Established Knowledge, Current Challenges and New Insights

Abstract: In the last two decades, a change in paradigm has taken place in the management of salivary gland diseases [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The underlying reason is that ultrasonic waves target specifically mineralized material leaving the organic material largely unaffected 7 . Intraductal shock-wave lithotripsy is effective but not the fastest method of treatment for difficult sialolithiasis, especially in the parotid gland which may require increased efforts using combination treatment 6 , 9 . In a retrospective study, sialolithiasis was found to be the most frequent pathology requiring the extirpation of the submandibular gland, accounting for 73.5% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying reason is that ultrasonic waves target specifically mineralized material leaving the organic material largely unaffected 7 . Intraductal shock-wave lithotripsy is effective but not the fastest method of treatment for difficult sialolithiasis, especially in the parotid gland which may require increased efforts using combination treatment 6 , 9 . In a retrospective study, sialolithiasis was found to be the most frequent pathology requiring the extirpation of the submandibular gland, accounting for 73.5% of cases.…”
Section: Introductionmentioning
confidence: 99%